ANALISIS PRODUKSI DALAM PERSPEKTIF EKONOMI ISLAM(Studi Kasus Pada keripik Cinta Mas Hendro Kecamatan Gebang Kabupaten Langkat) - Nursani Alvia Siregar; Sabilla Cahya Kinanti (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the production process of a producer in processing his product which is reviewed based on Islamic economics. The research method used is a qualitative approach. Data collection techniques used in this study were interviews and observation. The subjects used were the owner of the Mas Hendro love chip business and his employees. The results of this study indicate that the process of making love chips follows the production rules in Islam. The owner uses halal ingredients, maintains cleanliness, does not use preservatives or food coloring, maintains the security and safety of his employees and consumers, gives alms by giving free food and drinks to consumers. Researchers hope that research can be useful, especially for producers to continue to pay attention to halal, hygiene and consumer health in making a product for the sake of achieving benefit